2019
DOI: 10.1088/1748-9326/ab1219
|View full text |Cite
|
Sign up to set email alerts
|

Towards applying N balance as a sustainability indicator for the US Corn Belt: realistic achievable targets, spatio-temporal variability and policy implications

Abstract: Gains in nitrogen use efficiency in the production of corn (Zea mays L.) remain low due to management constraints and difficulties in accurately predicting the optimum fertilizer application rate. Retailers and consumers are looking for robust sustainability indicators to help drive the industry towards more sustainable food production, including the simple input-output based 'N balance' metric. Seven-year simulations for 25 locations across five US Corn Belt States (NE, IA, MN, IL, IN) were conducted using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…There are growing efforts to use N balance as an indicator of potential N losses because it is a measure of anthropogenic N supply that exceeds crop N demand (McLellan et al., 2018; Sela et al., 2019; Tenorio et al., 2020). Recent studies have shown significant relationships between N balance and nitrous oxide and nitrate‐N leaching losses (McLellan et al., 2018; Omonode, Halvorson, Gagnon, & Vyn, 2017; Venterea, Coulter, & Dolan, 2016; Zhao, Christianson, Harmel, & Pittelkow, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are growing efforts to use N balance as an indicator of potential N losses because it is a measure of anthropogenic N supply that exceeds crop N demand (McLellan et al., 2018; Sela et al., 2019; Tenorio et al., 2020). Recent studies have shown significant relationships between N balance and nitrous oxide and nitrate‐N leaching losses (McLellan et al., 2018; Omonode, Halvorson, Gagnon, & Vyn, 2017; Venterea, Coulter, & Dolan, 2016; Zhao, Christianson, Harmel, & Pittelkow, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…the difference between N inputs and outputs) as an estimate of N losses to track changes in N fertilizer efficiency and decrease the environmental footprint of crop production (McLellan et al., 2018; Tenorio et al., 2020). Recent studies have shown that N balance is sensitive to changes in N rate and form in the U.S. Midwest (Sela, Woodbury, Marjerison, & van Es, 2019). However, little research has explored how N balance can be utilized within an integrated N management framework to help growers not only identify the potential for N deficiencies but also evaluate the risk of environmental N losses (Tenorio et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the attempt in modeling the complex environmental impacts from nutrient budgets, several relatively simple indicators have been developed based on nutrient budgets. For example, N surplus (also called N balance) of the Soil‐Plant system is directly affected by farmers' management practices and is proven to be significantly related to yield‐scaled N losses when aggregated over multiple sites and years (McLellan et al, ; Sela et al, ). However, it should be recognized that the N surplus is not always the best predictor of the actual environmental impacts of an individual farm for a given year, which is also largely affected by factors such as year‐to‐year weather variations and the legacy effects of N in the soil.…”
Section: Challenges In Informing Nutrient Managementmentioning
confidence: 99%
“…Another possibility is illustrated by a soil-based model for maize in the United States, which combines information on soils, yields, and each year's weather to inform farmers how much nitrogen to apply during the growing season. Papers have estimated potential reductions in nitrogen application using this model of 20-40 percent (Sela et al 2019(Sela et al , 2018. This model is commercially available to farmers in the United States today.…”
Section: Precision Agriculturementioning
confidence: 99%